- The sum, from
*i*=*a*to*i*=*b*, of a constant*c*is*c*(*b*−*a*+ 1). - The sum, from
*i*=*a*to*i*=*b*, of*i*itself is (*a*+*b*)(*b*−*a*+ 1)/2. - The sum, from
*i*=*a*to*i*=*b*, of*i*^{2}is (2*a*^{2}2*a**b*+ 2*b*^{2}+*b*−*a*)(*b*−*a*+ 1)/6. - The sum, from
*i*=*a*to*i*=*b*, of*i*^{3}is (*a*^{2}+*b*^{2}+*b*−*a*)(*a*+*b*)(*b*−*a*+ 1)/4.

Go back to the course homepage.

This web page was written in 2013 by Toby Bartels, last edited on 2013 December 2. Toby reserves no legal rights to it.

The permanent URI of this web page
is
`http://tobybartels.name/MATH-1600/2013f/summation/`

.